Receptor-activated Smad localisation in Bleomycin-induced pulmonary fibrosis. Issue 3 (2nd June 2006) - Higashiyama, Hiroyuki; Yoshimoto, Daisuke; Okamoto, Yuji; Kikkawa, Hideo; Asano, Satoshi; Kinoshita, Mine
Abstract : Background: Recent advances in fibrosis biology have identified transforming growth factor (TGF)-β type I receptor-mediated activation of Smads as playing a central part in the development of fibrosis. However, to date, there have been few studies that examined the localisation and distribution of receptor-activated Smads protein (R-Smads: Smad2 and 3) during the fibrosis progression. Aims: To histopathologically assess the time-course change of the localisation and distribution of the Smads protein in pulmonary fibrosis. Methods: Pulmonary fibrosis was induced by intranasal injection of bleomycin (0.3 U/mouse). Lungs were isolated 2, 5, 7, 9 and 14 days after bleomycin treatment. Histological changes in the lungs were evaluated by haematoxylin-eosin stain or Masson's trichrome stain, and scored. TGF-β1, Smad3 and phosphorylated Smad2 localisations in lung tissues were determined by immunohistochemistry. Results: The bleomycin treatment led to considerable pulmonary fibrotic changes accompanied by marked increase in TGF-β1 expression in infiltrating macrophages. With the progression in fibrosis (day 7–14), marked increases in Smad3-positive and pSmad2-positive cells were observed. There were intense Smad3-positive and pSmad2-positive signals localised to the nuclei of the infiltrating macrophages and to type II epithelial cells, and less intense signals in fibroblasts and hyperplastic alveolar/bronchiolar epithelial cells. Conclusions: The time-course data of TGF-β1 and R-Smads indicate that progressive enhancement of TGF-β1 signalling via R-Smad is activated in the process of fibrosis progression.